Physiological endocrinology and causes of disorders of the menstrual cycle - Eliza Haryanti; Legiran (Institute of Computer Science (IOCS), 2023)
The menstrual cycle is the result of a complex interaction between the hormonal system and the body's organs, namely the hypothalamus, pituitary, ovaries and uterus. Regular menstrual cycle is an indicator of women's reproductive health, changes in the menstrual cycle can be associated with ovarian-thyroid dysfunction and pituitary axis. This article aimsto understand the role of endocrinology in the process of the menstrual cycle as well as review the currently available literature on the causes of disorders of the menstrual cycle.The method used is Systematic Literature Review using the Preferred Reporting Items for Systematic Reviews (PRISMA) flow by collecting articles, according to those obtained from the PubMed database, Wiley Online Library, Science Direct and Cochrane, with the keywords